Effectiveness of Gelam Wood Liquid Smoke on the Retention and Absorption Preservatives in Terantang Wood (Campnosperma auriculatum (BI.) Hook.f) - Supriyati, Wahyu; -, Alpian; Samosir, July Sarana Dame; -, Yanciluk; Tanduh, Yusintha; Silvianingsih, Yosefin Ari (TROPICAL WETLAND JOURNAL, 2025)
Wood durability is a crucial factor in its utilization, especially in tropical regions with high humidity levels. Terantang wood is classified as lightweight wood with low resistance to wood-degrading organisms. Preservation using liquid smoke is one of the alternative methods to enhance the durability of Terantang wood. This study aims to evaluate the effectiveness of liquid smoke derived from Gelam wood (Melaleuca sp.) as a natural preservative for Terantang wood. The preservation process was conducted using a cold-soaking method for 48 hours with three different liquid smoke concentrations: 10%, 20%, and 30%. After treatment, the wood samples were dried and tested to determine their retention and absorption values. The results showed that increasing the liquid smoke concentration directly correlated with higher retention and absorption values. The 30% concentration exhibited the highest retention (0.055 g/cm³) and absorption (0.241 g/cm³), indicating superior effectiveness in enhancing wood durability. Retention was highest near the heartwood, while absorption was greater near the sapwood. These findings suggest that Gelam wood liquid smoke has significant potential as an eco-friendly and cost-effective wood preservative. Its use can serve as a safer alternative to synthetic preservatives, supporting more sustainable wood processing practices. Keywords: Liquid smoke, Gelam wood, Terantang wood, wood preservation, retention, absorption